2022
DOI: 10.3390/ijms23169074
|View full text |Cite
|
Sign up to set email alerts
|

Human RNASET2: A Highly Pleiotropic and Evolutionary Conserved Tumor Suppressor Gene Involved in the Control of Ovarian Cancer Pathogenesis

Abstract: Ovarian cancer represents one of the most malignant gynecological cancers worldwide, with an overall 5-year survival rate, being locked in the 25–30% range in the last decade. Cancer immunotherapy is currently one of the most intensively investigated and promising therapeutic strategy and as such, is expected to provide in the incoming years significant benefits for ovarian cancer treatment as well. Here, we provide a detailed survey on the highly pleiotropic oncosuppressive roles played by the human RNASET2 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…As shown in Figure 1c, an inconsistency of the DEPs in the CT26/SCID and CT26/BALB/c tumors was found. For example, PTEN [33], RBL1 [34], CDKN2AIP [35], RNASET2A [36], HINT1 [37], and PARP12 [38] are well-known tumor suppressors and were downregulated or absent in the CT26/SCID tumors (Table S1). The enriched signaling pathways involved in cell cycles, namely, PIP3-activated AKT signaling, mTOR signaling, WNT signaling, and MAPK activation, suggested that the manipulation of tumor growth was significantly changed in the NOD.SCID mice.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 1c, an inconsistency of the DEPs in the CT26/SCID and CT26/BALB/c tumors was found. For example, PTEN [33], RBL1 [34], CDKN2AIP [35], RNASET2A [36], HINT1 [37], and PARP12 [38] are well-known tumor suppressors and were downregulated or absent in the CT26/SCID tumors (Table S1). The enriched signaling pathways involved in cell cycles, namely, PIP3-activated AKT signaling, mTOR signaling, WNT signaling, and MAPK activation, suggested that the manipulation of tumor growth was significantly changed in the NOD.SCID mice.…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, as already mentioned, T2 ribonucleases display an impressive degree of evolutionary conservation, suggesting a crucial and very ancient biological role for this class of enzymes [ 65 ]. Furthermore, a great bulk of experimental evidence has been gathered in the last decades to suggest a marked oncosuppressive activity of the human RNASET2 protein in both in vivo and in vitro experimental settings ( Figure 1 E) [ 85 ]. Noteworthy, negative control of cell growth, induction of apoptosis, and a marked remodeling of the cell cytoskeleton (all representing biological processes deeply involved in tumor suppression) were consistently reported to be modulated by several members of the T2 RNase family from evolutionarily distant species, ranging from Saccharomyces cerevisiae to Homo sapiens.…”
Section: T2 Rnases: Biological Rolesmentioning
confidence: 99%